Les Modeling of a Diurnal Cycle - Rizza, Umberto; Mangia, C.; Miglietta, M.; Moscatello, A.; Carvalho, J. C.; Degrazia, G. A.; Puhales, F. S.; Filho, E. P. Marques (Ciência e Natura, 2007)
LES modeling of a diurnal cycle